2020
DOI: 10.3390/su122410318
|View full text |Cite
|
Sign up to set email alerts
|

Eucheuma cottonii Seaweed-Based Biochar for Adsorption of Methylene Blue Dye

Abstract: Pollution from dye containing wastewater leads to a variety of environmental problems, which can destroy plant life and eco-systems. This study reports development of a seaweed-based biochar as an adsorbent material for efficient adsorption of methylene blue (MB) dye from synthetic wastewater. The Eucheuma cottonii seaweed biochar was developed through pyrolysis using a tube furnace with N2 gas, and the properties were later improved by sulfuric acid treatment. The adsorption studies were conducted in a batch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 54 publications
1
28
0
Order By: Relevance
“…The result of isotherm analysis is shown in Figure S2 and Table S2 (Supplementary file). The maximum R 2 values of the tested isotherms indicated that the model mostly suits the experimental results [2,84]. Comparing the correlation coefficients for the three isotherm models obtained for biochar and magnetic biochar, the most suitable is the Langmuir model.…”
Section: Adsorption Isotherm Analysismentioning
confidence: 79%
See 1 more Smart Citation
“…The result of isotherm analysis is shown in Figure S2 and Table S2 (Supplementary file). The maximum R 2 values of the tested isotherms indicated that the model mostly suits the experimental results [2,84]. Comparing the correlation coefficients for the three isotherm models obtained for biochar and magnetic biochar, the most suitable is the Langmuir model.…”
Section: Adsorption Isotherm Analysismentioning
confidence: 79%
“…Water resources have been harmed by a variety of toxins, including heavy metals, dyes, surfactants, phenols, and other personal care chemicals [1][2][3]. Since heavy metal waste almost does not dissolve into harmless materials, it accumulates and is toxic to humans.…”
Section: Introductionmentioning
confidence: 99%
“…Research on biomass utilization as a fuel focuses on the utilization of biomass mainly form agro-waste for producing a solid fuel block called a briquette. It is considered as one of the available options to off-set the widening gap between the demand and the supply of energy, and considering the depleting nature of non-renewable energy sources from fossil fuels [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, some technologies and materials have shortcomings. As a result, it is imperative to develop safe, cost-effective, and long-lasting wastewater treatment materials [ 78 ].…”
Section: Waste-to-resource Potential Of Pocmentioning
confidence: 99%